2016
DOI: 10.1016/s2352-3018(16)30053-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for adherence and depression in patients with HIV: a three-arm randomised controlled trial

Abstract: Summary Background Depression, highly prevalent in HIV, is consistently associated with worse ART adherence. Integrating CBT for depression with adherence counseling using the “Life-Steps” approach (CBT-AD) has an emerging evidence base. The aim of the current study was to test the efficacy of CBT-AD. Methods We conducted a three-arm RCT (N=240 HIV-positive adults with depression), comparing CBT-AD to Life-Steps integrated with information and supportive psychotherapy (ISP-AD) (both 12 sessions), and to ETA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 25 publications
8
109
0
4
Order By: Relevance
“…The parent study was a 12-month, 3-arm randomized controlled efficacy trial (Safren et al 2016). The arms were 1) CBT-AD, 2) ISP-AD and 3) ETAU, as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parent study was a 12-month, 3-arm randomized controlled efficacy trial (Safren et al 2016). The arms were 1) CBT-AD, 2) ISP-AD and 3) ETAU, as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The parent study focused on CBT-AD versus ETAU and ISP-AD for depression and medication adherence in people living with HIV/AIDS (Safren et al, 2016). The parent study found that patients who were assigned to CBT-AD had greater improvements in adherence than did patients who had ETAU after treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and especially depression have consistently been associated with poor antiretroviral treatment (ART) adherence (Safren et al, 2016;Smith Fawzi et al, 2016;Tao et al, 2016;Tatum & Houston, 2016), and are linked to poor virological control and lower CD4 T cell counts (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research has documented the efficacy of cognitive-behavioral interventions targeting depression and substance use to optimize HIV/AIDS prevention [40,41]. However, the efficacy of smoking cessation interventions for PLHIV have been modest at best [42,43], and many have not been tailored to address the unique barriers to smoking cessation.…”
Section: Discussionmentioning
confidence: 99%